Flexibility and FMS: An empirical analysis - TOMBAK, Mihkel (Institutional Knowledge at Singapore Management University, 1988)
It is shown how the concerns of the managers of firms with flexible manufacturing system projects (FMS) differ from those of manufacturing firms without FMS projects. An economic model is developed from which two hypotheses are obtained. The first hypothesis is that firms were investing in FMS to deal with the variance in their inputs. The second proposition is that firms wished to use FMS to deal with the variance in their outputs. Through an analysis of manufacturing survey data it was found that firms planning to implement FMS were statistically more concerned about vendor quality and vendor lead times than non-FMS implementors. The FMS implementors also thought of their outputs as being too variable. Thus, it appears that the two hypotheses are empirically validated. However, it is also found that FMS implementors are planning on narrowing or standardizing their product lines. The inference drawn from these observations is that manufacturers in North America and Europe are using FMS for its ability to adapt to the variations in the system's inputs and not for product design changes.